Alfonso X, the Justinian of His Age : Law and Justice in Thirteenth-Century Castile - O'Callaghan, Joseph F. (Book collections on Project MUSE., 2019)
"A examination of Alfonso X, who created a Libro de las leyes, the Siete Partidas, a code of law that has had an enduring impact on the development of law and institutions over the centuries not only in the Iberian Peninsula but also throughout the Spanish-speaking world"--